Design and Analysis of a Quasi-Biaxial Solar Tracker - Yakang Liu; Zhiquan Xiao; Yu Huang; Yubo Ma; Zihan Yang (Energies)
Inspired by C. Alexandru, to achieve a balance between tracking accuracy and equipment cost and between single-axis tracking brackets and dual-axis tracking brackets, a kind of quasi-biaxial solar tracker, whose approximate two-axis motions are driven by a single motor, is studied in this paper. Firstly, considering the changes in the total number of sunny days and declination angle in a certain period of time, the characteristic day of the tracker in this period is set. Then, based on the variations in the Sun’s azimuth and elevation angle on the characteristic day, a quasi-biaxial solar tracker mechanism is designed. Its azimuth angle movement is directly driven by a single motor, while the elevation angle movement is driven by the same motor through a bevel gear and a cam mechanism. The solar irradiance of the photovoltaic module of the solar tracker is analyzed using PVsyst software. Through 3D modeling-aided design, a prototype of the solar tracker is built and then relative experiments are conducted to study the performance of the quasi-biaxial solar tracker. Simulation analysis and physical model experiments show that the quasi-biaxial solar tracker works and achieves a relative compromise between tracking accuracy and cost.